The SIESTA Trial: A Randomized Study Investigating the Efficacy, Safety, and Tolerability of Acupressure versus Sham Therapy for Improving Sleep Quality in Patients with End-Stage Kidney Disease on Hemodialysis. (21st February 2017) - Shen, Kunyu; Cho, Yeoungjee; Pascoe, Elaine M.; Hawley, Carmel M.; Oliver, Veronica; Hughes, Kathryn M.; Baer, Richard; Frazier, Jeremy; Jarvis, Elizabeth; Tan, Ken-Soon; Liu, Xusheng; Gobe, Glenda; et al.
Abstract : Objectives . To compare the effectiveness of real acupressure versus sham acupressure therapy in improving sleep quality in patients receiving hemodialysis (HD) or hemodiafiltration (HDF). Methods . A multicenter, single-blind, randomized controlled trial was conducted in two Australian dialysis units located in Princess Alexandra Hospital and Logan Hospital, respectively. Forty-two subjects with self-reported poor sleep quality were randomly assigned to real (n = 21 ) or sham (n = 21 ) acupressure therapy delivered thrice weekly for four consecutive weeks during routine dialysis sessions. The primary outcome was the Pittsburgh Sleep Quality Index (PSQI) score measured at week four adjusted for baseline PSQI measurements. Secondary outcomes were quality of life (QOL) (SF-8), adverse events, and patient acceptability (treatment acceptability questionnaire, TAQ). Results . The two groups were comparable on global PSQI scores (difference 0.19, 95% confidence interval [CI] −1.32 to 1.70) and on the subscale scores. Similar results were observed for QOL both in the mental (difference −3.88, 95% CI −8.63 to 0.87) and the physical scores (difference 2.45, 95% CI −1.69 to 6.58). There were no treatment-related adverse events and acupressure was perceived favorably by participants. Conclusion . Acupressure is a safe, well-tolerated, and highly acceptable therapy in adult hemodialysis patients in a Western healthcare setting with uncertain implications for therapeutic efficacy.